Clinical efficacy of phentolamine in the treatment of feeding intolerance in premature infants with low birth weight - Li, Hongya (Pak J Med Sci, 2020)
OBJECTIVE: To discuss the clinical efficacy of phentolamine in the treatment of feeding intolerance in premature infants with low birth weight. METHODS: Seventy-one low-birth-weight infants with feeding intolerance were randomly divided into the phentolamine group and the erythromycin group (38 patients and 33 patients, respectively). The infants were given basic treatment, such as gastric lavage, temporary fasting, nutritional support and abdominal massage. The phentolamine group was intravenously pumped with phentolamine as the basis of basic treatment, while the erythromycin group was given erythromycin as the basis of basic treatment. The time for gastrointestinal symptoms to disappear, the time the basic standard was reached, the time parenteral nutrition was used, the total time enteral feeding was implemented, the length of stay, and the increase in physical indexes according to the corrected gestational age of 40 weeks of the two groups were compared. RESULTS: There was no significant difference between the phentolamine group and the erythromycin group in vomiting disappearance time or the increase in physical indicators at the corrected gestational age of 40 weeks (P>0.05), while the abdominal distension disappearance time, the time of restoration to birth weight, the time to reach the basic standard, the total time of parenteral nutrition, the total time of enteral feeding, and the length of stay in the phentolamine group were shorter than those in the erythromycin group, with significant differences (P<0.05). CONCLUSION: Phentolamine has a significant effect on alleviating symptoms and shortening the treatment time while treating feeding intolerance in premature infants with low birth weight, without adverse events, so it is worthy of clinical promotion.